2018
DOI: 10.1021/acs.macromol.8b02069
|View full text |Cite
|
Sign up to set email alerts
|

Chain-End Functionalization with a Saccharide for 10 nm Microphase Separation: “Classical” PS-b-PMMA versus PS-b-PMMA-Saccharide

Abstract: Microphase-separated structures of block copolymers (BCPs) have attracted much attention as template materials for bottom-up nanofabrication. At the same time, chain-end modification has become a leading facile and efficient technique for fine-tuning the morphologies of microphase-separated structures generated from BCPs. Herein, we describe the preparation of well-defined polystyrene-block-poly­(methyl methacrylate)­s (PS-b-PMMAs) bearing highly hydrophilic mono/oligosaccharide moieties at their PMMA chain en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…Further, while bulk thermotropic DG phases have been previously observed for glycolipids, [5, 13d] to the best of our knowledge, this same nanostructured morphology has not yet been reported for any class of saccharide‐hydrocarbon within an ultra‐thin film construct. Accordingly, a variable temperature synchrotron 2D GISAXS investigation of ultrathin films of 1 a that are supported on hydrophobic c‐Si substrates was conducted using various temperature ramp and jump profiles in order to determine if the unique stability observed in the bulk for the HPL and DG phases also occurs in ultrathin films.…”
Section: Figuresupporting
confidence: 66%
“…Further, while bulk thermotropic DG phases have been previously observed for glycolipids, [5, 13d] to the best of our knowledge, this same nanostructured morphology has not yet been reported for any class of saccharide‐hydrocarbon within an ultra‐thin film construct. Accordingly, a variable temperature synchrotron 2D GISAXS investigation of ultrathin films of 1 a that are supported on hydrophobic c‐Si substrates was conducted using various temperature ramp and jump profiles in order to determine if the unique stability observed in the bulk for the HPL and DG phases also occurs in ultrathin films.…”
Section: Figuresupporting
confidence: 66%
“…10,11 It should be noted here that previous studies by our group and Sita's group revealed that block copolymers (BCPs) consisting of hydrophobic polymers and oligosaccharides readily self-assembled into microphase-separated structures due to the strong segregation between the blocks, which was further enhanced by the rigid rod nature of the oligosaccharide. [12][13][14][15][16][17][18][19][20][21][22][23] We therefore envisioned that the integration of a rubbery hydrophobic polymer at the middle block and oligo/polysaccharide hard segments at the outer blocks could provide a novel bio-based elastomer, in which the microphase-separated carbohydrate hard domains act as a physical crosslink for the rubbery chains.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of Mal 3 –alkyne 1 has already been reported elsewhere. 35 The mixture of Mal 3 (500 mg, 991 μmol) and PA (900 μL, 14.1 mmol) was stirred at room temperature. The consumption of Mal 3 was monitored by TLC (silica gel 60 F 254 , CH 3 CN/H 2 O = 2:1).…”
Section: Methodsmentioning
confidence: 99%